Optimal tigecycline dosage regimens in patients infected with carbapenem-resistant Enterobacteriaceae - Santimaleeworagun, Wichai; Saelim, Weerayuth; Thunyaharn, Sudaluck; Hemapanpairoa, Jatapat; Juntanawiwat, Piraporn (Science, Engineering and Health Studies, 2020)
We aimed to evaluate the minimum inhibitory concentration (MIC) values of tigecycline for carbapenem-resistant Enterobacteriaceae (CRE) and to identify a potential regimen for achieving target values of the area under the curve from 0 to 24 h divided by MIC (AUIC) 10.1 and 6.9. CRE clinical isolates were first obtained from blood specimens from each patient admitted to Phramongkutklao Hospital, Thailand, from October 2017 to October 2018. Tigecycline MIC was assayed using broth microdilution method. The tigecycline dosage regimens for critically ill patients were simulated using the Monte Carlo technique. The tigecycline dose that met 90% of probability of target attainment (PTA) and cumulative fraction of response (CFR) was considered as an appropriate regimen. Sixty-one CRE isolates were included. MIC50, MIC90, and MIC range for tigecycline were 0.5, 1.0, and 0.25-4.0 µg/mL, respectively. Regarding AUIC 10.1 target, the dose of 150-200 mg/day achieved the PTA target for isolates with a MIC of 0.5 µg/mL. Whereas, for AUIC 6.9, a dose of 200 mg/day covered CRE with an MIC of 1.0 µg/mL. For CFR >90%, only a dose of 200 mg/day was capable of achieving the AUIC target of 6.9. None of the studied regimens yielded a CFR >90% for the AUIC target of 10.1. Tigecycline seems to be a possible treatment for CRE; however, tigecycline 200 mg daily may be optimized to cover the CRE isolates with a MIC 1 µg/mL.